Analisis Kualitas Data dalam Keputusan Pembelian Konsumen - Baihaqi, Ahmad; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the midst of rapid digital development, online and online shopping transactions have become an inseparable part of society. The ease of access to various products and services makes consumers have the freedom to make their choices. However, a phenomenon that often arises is consumer behavior that moves from one store to another, both online and offline. One of the factors causing this is the poor quality of data owned by a company. Inaccurate, incomplete, or irrelevant data can hinder companies in understanding the needs and preferences of their consumers, resulting in less than optimal services. Data quality plays a very important role in building effective communication, as well as targeted decision-making.Poor data quality can affect a person’s purchasing decisions. Accurate data makes it easier for companies to improve services, understand consumer needs, and build sustainable loyalty relationships. Therefore, it is important for every company to maintain the integrity and accuracy of data in order to create a satisfying shopping experience and maintain customer loyalty.